Eksistensi Kepedulian Sosial dalam Membangun Ukhuwah Wathaniyah pada Masyarakat Kec. Tanjung Beringin, Kab. Serdang Bedagai - Mila Rima Dani; Mardhiah Abbas; Zulkarnain Zulkarnain (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research examines the existence of social care in building ukhuwah wathaniyah in the community of Tanjung Beringin District, Serdang Bedagai Regency. Ukhuwah wathaniyah, as a concept of brotherhood that transcends ethnic and religious barriers, is an important foundation in strengthening social relations in a diverse society. This research focuses on how forms of social care, such as gotong royong, humanitarian assistance, and cooperation between citizens play a role in creating harmony and solidarity in the midst of society. The method used in this research is a qualitative approach with data collection through in-depth interviews, observation, and documentation. The data obtained were analyzed using descriptive analytical method to describe the patterns of social interaction that support ukhuwah wathaniyah. The research findings show that social care in Tanjung Beringin Sub-district is a key factor in strengthening ukhuwah wathaniyah. The local community shows a strong commitment to maintaining and improving social harmony through various activities that involve all levels of society. The results of this study provide a deeper understanding of the importance of social care in building ukhuwah wathaniyah in a multicultural society. It is hoped that this research can serve as a reference for policy makers and related parties in formulating inclusive and sustainable social development strategies in Tanjung Beringin Sub-district as well as other areas with similar social characteristics.